EFFECT OF DEEP BREATH RELAXATION ON THE ANXIETY AMONG THIRD TRIMESTER PREGNANT WOMEN IN MOJOKERTO DISTRICT, INDONESIA: A QUASI EXPERIMENT - Zulfa Rufaida; Ratri Istiqomah; Sri Wardini Puji Lestari (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2023)
Background: Factors that contribute to the occurrence of lengthy labor are power: the strength of the mother when giving birth is ineffective and the mother's psychology is unready for childbirth. Purpose. Psychologycally, an unrelaxed mother can pass this condition on to her baby so that the baby feels easily agigated. Methods: Used a quasi-experimental design with pretest-post-test none-quivalent control group design. The sample was divided into 2 groups (treatment and control), 15 people per group. Sampling was undertaken with purposive sampling technique. An anxiety measurement instrument was the Zung Self-Rating Anxiety Scale (SAS/SRAS). Results: The result of the paired t-test with a significance level of a: 0.05 was a significance of 0.007<0.05 with a confidence interval value (95% CI): 8.83-13.70, thus Ha was accepted. Results showed that there was effect of deep breathing relaxation on the anxiety score of pregnant woman. Conclusion: Deep breathing relaxation has the advantage of reducing anxiety, both physical and emotional stress, relieving pain, and insomnia. The importance of managing deep breathing relaxation non-pharmacological therapy was to reduce anxiety in pregnant woman, since deep breathing relaxation therapy can be done independently and relatively easy to do. Abstrak Latar Belakang: Faktor yang berkontribusi akan terjadinya persalinan lama adalah power yaitu kekuatan ibu saat melahirkan tidak efektif dan psikologis ibu yang tidak siap menghadapi persalinan. Tujuan: Secara psikologis, ibu yang tidak tenang dapat menurunkan kondisi tersebut kepada bayinya sehingga bayi mudah merasa gelisah. Metode: Metode penelitian menggunakan quasi experiment design pretest-posttest noneequivalent control group design. Sampel dibagi 2 kelompok (perlakuan dan kontrol) yaitu 15 orang per kelompok. Sampling dengan tehnik purposive sampling. Instrumen pengukuran kecemasan dengan Zung Self-Rating Anxiety Scale (SAS/SRAS). Hasil: Hasil paired t test dengan tingkat nilai kemaknaan a: 0,05 signifikansi 0,007<0,05 dengan nilai confident interval (CI 95%): 8.83-13.70, sehingga Ha di terima, ada pengaruh relaksasi napas dalam dengan skor kecemasan ibu hamil. Kesimpulan: Relaksasi napas dalam memiliki suatu kelebihan untuk mengurangi kecemasan stres baik fisik maupun emosional, menghilangkan nyeri, dan insomnia. Pentingnya penatalaksanaan terapi nonfarmokologis relaksasi napas dalam untuk menurunkan kecemasan pada ibu hamil, karena terapi relaksasi napas dalam dapat dilakukan mandiri, relatif mudah dilakukan.